1997
DOI: 10.1046/j.1365-2109.1997.t01-1-00837.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA fingerprinting in Indian major carps and tilapia by Bkm 2(8) and M13 probes

Abstract: DNA fingerprints were obtained in three species of commercially important freshwater fishes, Labeo rohita (Hamilton). Catla catla (Hamilton) and Oreachromis mossambicus (Peters), using Bkm 2(8) and M13 multilocus probes. Bkm 2(8) gave a higher number of bands when compared with M13. However, the number of bands obtained by each probe in O. mossambicus was similar. The higher band‐sharing coefficient observed in this species may be attributed to inbreeding as it arose from a small founder population. In L rohit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Cloning of chromosomal growth hormone gene from different Labeo species Genomic DNA was prepared from the stored blood samples by proteinase-K digestion and phenol extraction (Majumdar et al 1997). Oligonucleotide primers were designed from the sequenced L. rohita GH gene obtained by us (Genbank Accession AF 418921), including both 5 0 and 3 0 untranslated regions encompassing the poly-A signal.…”
Section: Methodsmentioning
confidence: 99%
“…Cloning of chromosomal growth hormone gene from different Labeo species Genomic DNA was prepared from the stored blood samples by proteinase-K digestion and phenol extraction (Majumdar et al 1997). Oligonucleotide primers were designed from the sequenced L. rohita GH gene obtained by us (Genbank Accession AF 418921), including both 5 0 and 3 0 untranslated regions encompassing the poly-A signal.…”
Section: Methodsmentioning
confidence: 99%
“…In marine fishes, speciesspecific allozyme markers were developed to resolve the taxonomic ambiguity in marine catfish species such as Tachysurus maculatus and T. subrostratus. DNA fingerprints of Indian major carps were obtained using banded Krait minor satellite 3 [BKM(3)] and M13 multilocus probes (Majumdar et al 1997) and using RAPD markers (Barman et al 2003;Das et al 2005b). Menezes et al (2002) identified diagnostic loci suitable for stock delineation and species identification among five nemipterid fish species from the Indian coast using allozyme analysis.…”
Section: Use Of Molecular Data For Preserving Fish Diversitymentioning
confidence: 99%
“…In hybridization study, growth comparison of the reciprocal hybrids is important because they are seldom the same (Tave, Jayaprakash, & Smitherman, 2007). Various genetic studies have been carried out in L. rohita, including DNA fingerprinting by using a sex specific satelite DNA [Bkm 2(8)] and a minisatelite DNA [M13] probes, (Majumdar, Ravinder, & Nasaruddin, 1997), detection of hybrids in the three Indian major carp (catla, rohu and mrigal) using ribosomal DNA RFLP with Xenopus laevis rDNA as a probe (Padhi & Mandal, 1997), RAPD analysis (Barman et al, 2003;Islam & Alam, 2004) and allozyme analysis (Alam, Akanda, Khan, & Alam, 2002;Khan, Rahman, A1am, & Bhuiyan, 2006). Previous studies involving allozyme and RAPD analysis revealed relatively low levels of intra and inter-population genetic variation in the three river populations of rohu and catla (Alam et al, 2002;Islam & Alam, 2004;Islam, Ahmed, Azam, & Alam, 2005) and a wide spread hybridization practices in the hatchery stocks among the three Indian major carp species (Simonsen, Hansen, Mensberg, Serder, & Alam, 2005).…”
Section: Introductionmentioning
confidence: 99%